The effect of adenosin triphosphate in reducing duration of first stage of labour - R. Soeharyono, R. Soeharyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
A double blind randomized clinical trial was done at Dr. Sardjito General Hospital, Yogyakarta, to evaluate the effect of adenosin triphosphate (ATP) in reducing duration of first stage of labour and incidence of complicated labour. The subjects of the study were 100 normal parturients fulfilling the inclusions criteria of 20 to 30 years of age, parity less than 4, gestational age of 38 to 42 weeks, in a latent period with intact membranes and an estimated body weight of 2500 to 3500 gram. They were randomly allocated into treatment (50 cases) and control (50 cases) groups. The treatment group received 1 ampule ATP intramuscularly during the latent period of labour and was repeated in every 6 hours if the cervical dilatation had not completed yet. The control groups were given placebo of physiological saline solution in the same procedure. The duration of the first stage of labour was calculated from the onset of labour until fully dilatation of the cervix. Those with complicated labour pregnancy was terminated and was analyzed in a separate group. Other variables included in the analysis were age, parity, fertility states, hemoglobin concentration, nutritional states, and infant body weight. Among 100 parturients, 10 cases were terminated due to unprogress labour: of 3 cases from the treatment group and 7 other cases from control group. The adenosin triphosphate use could shorten the duration of first stage of labour by 1.5 Â± 1.3 hours compared to the control group. Adenosin triphosphate was effective in reducing the duration of labour and the incidence of complicated labour.Key words: adenosin triphosphate (ATP) - first stage of labour - complicated labour